2022
DOI: 10.54103/2039-4942/15607
|View full text |Cite
|
Sign up to set email alerts
|

Going Deeper Into Modern and Fossil Crocodilian Tooth Microanatomy: What Can Be Inferred of Palaeoenvironment and Taphonomy From Histochemical Analyses?

Abstract: Teeth provide information about the evolutionary pathway of an organism, its biology and habitat. This is the case even of fossilized teeth, since they have perdurable biomineralized structures, as biological apatite. The material that has been selected for this study comprises teeth from modern crocodilian individuals and extinct Cretaceous crocodylomorphs from Lo Hueco site. Microanatomy, histochemistry and crystallographic nature of enamel, dentine and cementum have been characterized by Polarized Light Mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…The vascular canals sometimes anastomose to form reticular, circumferential, or radial organizations. Similar types of vascularization patterns have also been reported for other crocodylians ( A. mississippiensis , Klein et al, 2009; Lee, 2004; Rainwater et al, 2021; Werning, 2013; Woodward et al, 2014; Caiman yacare , Andrade et al, 2018; and Crocodylus niloticus , Audije‐Gil et al, 2023; Chinsamy, 1991). Some of these earlier studies also reported a concentric arrangement of the LVCs in other reptiles (e.g., Botha & Botha, 2019; Navarro et al, 2023; Pellegrini et al, 2021; Pereyra, 2022; Werning, 2013).…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…The vascular canals sometimes anastomose to form reticular, circumferential, or radial organizations. Similar types of vascularization patterns have also been reported for other crocodylians ( A. mississippiensis , Klein et al, 2009; Lee, 2004; Rainwater et al, 2021; Werning, 2013; Woodward et al, 2014; Caiman yacare , Andrade et al, 2018; and Crocodylus niloticus , Audije‐Gil et al, 2023; Chinsamy, 1991). Some of these earlier studies also reported a concentric arrangement of the LVCs in other reptiles (e.g., Botha & Botha, 2019; Navarro et al, 2023; Pellegrini et al, 2021; Pereyra, 2022; Werning, 2013).…”
Section: Discussionsupporting
confidence: 67%
“…Below, we highlight the distinctive osteohistology at different stages of ontogeny: bone tissues formed during embryonic growth, histological variation among the hatchlings, juvenile to adult growth, the variation in growth among mature individuals. Audije-Gil et al, 2023;de Buffrenil & Castanet, 2000;Castanet & Baez, 1991;Horner et al, 2001;Hugi & Sánchez-Villagra, 2012;Lee, 2004;amphibians, Bruce & Castanet, 2006;and mammals, Chinsamy & Hurum, 2006;Garrone et al, 2019;Nacarino-Meneses & Köhler, 2018;Woolley, et al, 2021), and among crocodylians was described in humerus of specimens of Crocodylus niloticus (Audije-Gil et al, 2023), in tibia and femora of A. mississippiensis (Horner et al, 2001;Lee, 2004).…”
Section: Osteological Changes Through Ontogenymentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, in this second part of the review, the main focus is to give an overview of the use of synchrotron X-ray applications in human dental research (for animal species, numerous studies have been carried out on a variety of species and fossils [ 256 , 257 , 258 , 259 , 260 , 261 , 262 , 263 , 264 , 265 , 266 , 267 , 268 , 269 , 270 , 271 , 272 , 273 , 274 , 275 , 276 , 277 , 278 , 279 ], as well as studies on biofilms [ 280 , 281 , 282 , 283 ]). This review was performed by searching several platforms, including ScienceDirect, Web of Science, and SciFinder.…”
Section: Synchrotron (Circular Particle Accelerator)mentioning
confidence: 99%